2022
DOI: 10.2147/dddt.s357891
|View full text |Cite
|
Sign up to set email alerts
|

The Flavagline Compound 1-(2-(dimethylamino)acetyl)-Rocaglaol Induces Apoptosis in K562 Cells by Regulating the PI3K/Akt/mTOR, JAK2/STAT3, and MAPK Pathways

Abstract: Purpose Chronic myelogenous leukemia (CML) is a hematological malignancy with increased proliferation of cells of the myeloid series. This can disrupt normal hematopoiesis. The 1-(2-(dimethylamino)acetyl)-rocaglaol (MQ-16) is a new synthetic flavagline compound that showed promising activity in chronic myeloid leukemia K562 cells. This study aims to analyze the underlying mechanisms of MQ-16 against CML. Methods Growth, cell cycle progression, and apoptosis were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…JAK2/STAT3 is a classical pathway responsible for the transcriptional activation and signal transduction of STAT 59 . Upon activation, the JAK/receptor complex facilitates the phosphorylation of STAT proteins, which then translocate to the nucleus and regulate the expression of downstream target genes 60 , 61 . In AD-induced acute lung injury, IL-22 inhibits Ang II-mediated pulmonary microvascular endothelial cell apoptosis and downregulates STAT3 expression and intranuclear delivery.…”
Section: Discussionmentioning
confidence: 99%
“…JAK2/STAT3 is a classical pathway responsible for the transcriptional activation and signal transduction of STAT 59 . Upon activation, the JAK/receptor complex facilitates the phosphorylation of STAT proteins, which then translocate to the nucleus and regulate the expression of downstream target genes 60 , 61 . In AD-induced acute lung injury, IL-22 inhibits Ang II-mediated pulmonary microvascular endothelial cell apoptosis and downregulates STAT3 expression and intranuclear delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The MEK inhibitor, on the other hand, enhances growth inhibition and cell death in Calu-6 lung cancer cells treated with ATO ( 56 ). JNK and p38 will be activated while ERK is suppressed in order to cause apoptosis in cancer cells, as evidenced by the effects of dominant-interfering or constitutively active versions of particular JNK-p38 and ERK signaling pathway components ( 57 ). Lee et al ( 58 ) reported that As 4 S 4 could decrease the expression levels of specific proteins, such as Bcl-2 and p-ERK in the KRAS mutant cell lines A549 and H460 and exert an antiangiogenic effect, which led to the inhibition of tumor cell growth, proliferation, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 99%